The woman in white eaudiobook - Collins, Wilkie (Tantor Media, 2010)
One of the greatest mystery thrillers ever written, Wilkie Collins's The Woman in White was a phenomenal bestseller in the 1860s, achieving even greater success than works by Charles Dickens. Full of surprise, intrigue, and suspense, this vastly entertaining novel continues to enthrall audiences today. The story begins with an eerie midnight encounter between artist Walter Hartright and a ghostly woman dressed all in white who seems desperate to share a dark secret. The next day Hartright, engaged as a drawing master to the beautiful Laura Fairlie and her half sister, tells his pupils about the strange events of the previous evening. Determined to learn all they can about the mysterious woman in white, the three soon find themselves drawn into a chilling vortex of crime, poison, kidnapping, and international intrigue. Masterfully constructed, The Woman in White is dominated by two of the finest creations in all Victorian fiction—Marion Halcombe, dark, mannish, yet irresistibly fascinating, and Count Fosco, the sinister and flamboyant "Napoleon of Crime."